2013
DOI: 10.1080/14693062.2014.859501
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder engagement in adaptation interventions: an evaluation of projects in developing nations

Abstract: Institution-oriented, top-down and community-oriented, bottom-up stakeholder approaches are evaluated for their ability to enable or constrain the implementation of adaptation in developing nations. A systematic review approach is used evaluate the project performance of 18 adaptation projects by three of the Global Environment Facility's (GEF) adaptation programmes (the Strategic Priority for Adaptation (SPA), the Special Climate Change Fund (SCCF), and the National Adaptation Programs of Action (NAPA)) accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 53 publications
0
71
0
2
Order By: Relevance
“…Wamsler (2017) demonstrated that the types of stakeholders engaged influence the outcomes of the process and went further to highlight that the power constellation and the broader governance context shape the stakeholder engagement process. Sherman and Ford (2014) recommended careful consideration of the inclusion and detail of stakeholder engagement strategies in climate change adaptation projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wamsler (2017) demonstrated that the types of stakeholders engaged influence the outcomes of the process and went further to highlight that the power constellation and the broader governance context shape the stakeholder engagement process. Sherman and Ford (2014) recommended careful consideration of the inclusion and detail of stakeholder engagement strategies in climate change adaptation projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Once each group has finished discussing each adaptation option, each mediator would then share the results of his/her group to the rest of the audience and the focus group discussion would continue in a plenary session until a consensus is reached on the results [37]. It is important to note that building consensus may be difficult if stakeholders have different political interests and internal power dynamics; therefore, we stress the need for a sensitivity analysis and that more time is spent on training volunteer stakeholders in order for them to anticipate the complexities of participatory processes [54,68]. Next, we detail the application of each method of the framework as well as the sensitivity analysis.…”
Section: Application Of the Adaptation Prioritization Frameworkmentioning
confidence: 99%
“…Definitions of short-, mid-and long-term will vary amongst communities, decision makers, and community representatives, and need to be defined in partnership before conducting MCDA. Further, clear communication with knowledge users regarding the expected timescale of the adaptation option is important in order to manage expectations and maintain the legitimacy of the adaptation intervention [54].…”
Section: Timescale: How Long Does the Adaptation Option Take To Implementioning
confidence: 99%
“…To date, community engagement/empowering research within the developing regional context is limited to validating the importance of community driven approach. A number of scholars have criticized a narrowness of managerial approach in addressing multiple issues related to developing regional contexts such as weak institutions, high level of poverty and competing interests of stakeholders (e.g., Head, 2007;Sherman & Ford, 2014). We develop an organizational framework of inclusion for integrating business and disenfranchised community for community growth that illustrates the need for four types of managerial accountabilities, taking into account the unique contextual issues of developing regions -weak institutions, high level of poverty and competing interests of stakeholders.…”
Section: Community Psychology Perspective and Inclusionmentioning
confidence: 99%